2005
DOI: 10.3168/jds.s0022-0302(05)73005-8
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profiles Associated with Microbial Colonization of Freshly Ingested Grass and Rumen Biohydrogenation

Abstract: Two in situ studies were conducted to examine the use of odd-chain fatty acid profiles to study microbial colonization of freshly ingested herbage in the rumen as well as fatty acid biohydrogenation. In the first study, fresh perennial ryegrass was subjected to a range of sample preparation methods before incubation in the rumen for 2 or 7 h. In the second study, fresh perennial ryegrass was chopped into 1-cm lengths and incubated in polyester bags in the rumen for 2, 8, and 24 h. After removal of bags from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 31 publications
2
42
1
3
Order By: Relevance
“…Bessa et al (2009) studied the FA composition of LAB, SAB1 and SAB2 with the aim of identifying these bacteria from their FA profile, and found marked differences in FA composition between LAB and SAB (i.e., detachable plus undetachable solid associated bacteria) populations, consistent with others (Bauchart et al, 1990a;Kim et al, 2005;Vlaeminck et al, 2006b). LAB had a lower FA content and a higher proportion (g/kg FA) of odd branched chain FA (OBCFA) than did SAB, which had a higher proportion of C18 biohydrogenation derived FA (C18:0; especially trans C18:1 and CLA).…”
Section: Lipolysis and Biohydrogenationsupporting
confidence: 74%
See 1 more Smart Citation
“…Bessa et al (2009) studied the FA composition of LAB, SAB1 and SAB2 with the aim of identifying these bacteria from their FA profile, and found marked differences in FA composition between LAB and SAB (i.e., detachable plus undetachable solid associated bacteria) populations, consistent with others (Bauchart et al, 1990a;Kim et al, 2005;Vlaeminck et al, 2006b). LAB had a lower FA content and a higher proportion (g/kg FA) of odd branched chain FA (OBCFA) than did SAB, which had a higher proportion of C18 biohydrogenation derived FA (C18:0; especially trans C18:1 and CLA).…”
Section: Lipolysis and Biohydrogenationsupporting
confidence: 74%
“…Indeed, except for C17:1 which is endogenously synthesized by the action of 9 desaturase (Fievez et al, 2003), C15:0 and C17:0 are partially de novo synthesized (Vlaeminck et al, 2006a;Cabrita et al, 2007). OBCFA have been confirmed to be extremely relevant as markers of ruminal microbial activity, especially when effects of incubation time of substrate or sample preparation methods of microbial colonization/contamination in vivo and in vitro need to be evaluated (Kim et al, 2005). Attempts to validate relationships between rumen OBCFA output and milk OBCFA are mixed compared with microbial markers such as diaminopimelic acid (DAPA) and purine bases (PB; Fievez et al, 2003).…”
Section: Odd and Branched Chain Fatty Acids: A New Frontier In The Stmentioning
confidence: 99%
“…Examples included fatty acids and their methyl esters such as hexadecanoic acid, octadecatrienoic acid, octadecenoic acid, and pentadecanoic acid, which are relatively common essential oils in higher plants. Hexadecanoic acid is one of the major odd-and branched-chain fatty acids in rumen microorganisms (21).…”
Section: Discussionmentioning
confidence: 99%
“…Branched-and odd-chain fatty acids Use of branched-and odd-chain fatty acids as microbial markers have indicated that differences in the flows of these particular fatty acids may represent variations in rumen microbial ecology (Kim et al, 2005). In the current study, flows of these particular fatty acids at duodenum, C13:0, C15:0, C15:0 anteiso, C15:0 iso and C17:0 in particular, differed between red clover and grass silage diets, which suggests that forage species may have altered the rumen microbial population.…”
Section: Rumen Functionmentioning
confidence: 99%